Quality of Life and Level of Depressive Symptoms in the Geriatric Population - Yeşim Akyol,; Dilek Durmuş,; Cengizhan Doğan,; Yüksel Bek,; Ferhan Cantürk, (Archives of Rheumatology, 2010)
Objective: An increase in the prevalence of physical and mental disorders, such as depression with aging, together with environmental factors, may cause deterioration in the quality of life. The present study was conducted to investigate the effects of the general state of health and personal characteristics on quality of life in elderly patients, and to evaluate the relationship between the level of depressive symptoms, pain intensity, and quality of life. Materials and Methods: One hundred twenty individuals ≥65 years of age were included in the study. All subjects were evaluated using a questionnaire form, including items about demographic and clinical information (doctor diagnosed of chronic diseases, such as diabetes mellitus, hypertension, cardiovascular diseases, and hyperlipidemia). The intensity of pain was assessed by a visual analogue scale (VAS), quality of life was assessed by the Short Form-36 (SF-36), and the level of depressive symptoms was assessed by the Geriatric Depression Scale (GDS). Results: The mean age of the subjects was 71.53±4.69 years; 88.3% (n=106) were females and 11.7% (n=14) were males. Chronic diseases were present in 80.8% of the subjects (n=97) and hypertension was the most prevalent disease (49.7%). There was a significant negative correlation between quality of life and pain intensity and level of depression. When evaluated according to educational status, significant differences were found between the groups in some quality of life parameters (physical functioning, social functioning, mental health, and bodily pain) and the GDS (p<0.05). When evaluated according to the presence of chronic diseases, significant differences were also found between the groups in physical functioning, social functioning, vitality, and bodily pain subscales of quality of life measures and the GDS (p<0.05). Conclusion: The presence of a chronic disease and low educational status reduce the quality of life and increase the level of depression in the elderly. Quality of life is negatively affected with the level of depression and the pain intensity. Efforts to improve these conditions may contribute to improving the quality of life of elderly individuals. (Turk J Rheumatol 2010; 25: 165-73)